Identification of the factors of socio-cultural environment affecting the physical activity students: a qualitative study - Akram Sadeghpour; Mohammad Ehsani; marjan saffari; Fereshteh Zamani Alavijeh (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objectives: Studies of variables related to the levels of student physical activity can provide an active lifestyle throughout their lives. Thus, this study was conducted to identify the factors affecting the socio-cultural environment in physical activity of students of Iranian University of Medical Sciences. Materials and Methods: This study was a qualitative content analysis with a deductive-inductive approach. Participants were 23 individuals (20 males and 3 females) of physical activity experts and 16 students (7 females and 9 males) who reached theoretical saturation with 21 interviews with professors and 2 focal sessions with students. Samples (experts) were selected based on the snowball sampling method and the students were randomly assigned to the focal sessions. The interviews were conducted in a semi-structured manner and the data were analyzed at the same time as the data were collected and manually analyzed. Results: In the study of social factors related to physical activity, 3 main categories, the role of family and friends, with subcategories (accompaniment, role modeling, facilitator, instrumental and direct support), coaches and expert support (communication support, support Competence and independence, reinforcing social morality, and normative and cultural barriers (cultural gender rules and stereotypes and gender differences) were extracted. Conclusion: The identified variables of research are important in the realization of student physical activity behavior and help relevant organizations such as the Ministry of Health and Medical Education, universities and other related areas to plan health promotion and create a healthy lifestyle for students.